Relationship Between Serum Concentration of Adrenomedullin and Myocardial Ischemic T Wave Changes in Patients With Lung Cancer - Wu, Chen; Lin, Da-wei; Jiang, Yi-wen; Jiang, Feng; Wang, Zhao-xia; Wang, Yao-sheng (Frontiers in Cardiovascular Medicine, 2022)
Background: Lung cancer patients are at increased risk for the development of cardiovascular diseases. Molecular markers for early diagnosis of cardiac ischemia are of great significance for early prevention of cardiovascular events for lung cancer patients. Through evaluating the relation between adrenomedullin (ADM) and myocardial ischemic T wave change, it is confirmed that the clinical value of circulating ADM as a predictor of myocardial ischemia in patients with lung cancer. Methods: We enrolled the lung cancer patients & healthy people from 2019-2021 and extracted the detailed ECG parameter. After adjustment for potential confounders, logistic regression was used to assess the association of clinical data. We performed analyses on the differences in T wave between lung cancer patients and healthy people, relation between T wave and ADM among lung cancer patients. Receiver operator characteristic (ROC) curves were drawn to confirm diagnostic value of biomarkers. Results: After adjusted for potential confounders, the incidence of T wave inversion or flat within lung cancer patients were higher than healthy people (OR: 3.3228, P=0.02). Also, further analyze the data of lung cancer patients found that the ADM in lung cancer patients with T wave inversion or flat was higher than those with normal T wave (189.8 ± 51.9 vs. 131.9 ± 38.4, P<0.001). The ROC curve had an area under the ROC curve of 0.8137. Conclusions: Among lung cancer patients, the serum ADM concentration has association with the incidence of abnormal T wave. ADM might be a potentially valuable predictor for heart ischemia in lung cancer patients.